Broadband and Efficient Diffraction. Issue 7 (8th July 2013) - Ribot, Céline; Lee, Mane‐Si Laure; Collin, Stéphane; Bansropun, Shailendra; Plouhinec, Patrick; Thenot, Didier; Cassette, Simone; Loiseaux, Brigitte; Lalanne, Philippe
<x xml:space="preserve">Abstract</x> By exploiting the highly chromatic behavior of semiconductor structures with mesoscopic dimensions only slightly smaller than the wavelength, efficient diffraction is maintained over almost one octave. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>